THE ROLE OF FAMILY SUPPORT AND THE ROLE OF CADRES IN HYPERTENSION MANAGEMENT EFFORTS AT POSYANDU FOR THE ELDERLY - Suharyanta, Dwi; Widiyaningsih, Dwi; Sugiono (LPPM AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA, 2025)
Background : Hypertension in one degenerative diseases that has high mortality level and influences the quality of life and the productivity of elderly. The Physicaal changing decrease of the elderly causes health problem that is caysed by aning process and that often happens in the cardiovaskular system is hypertension disease. Problems were found in the village Trimulyo is less active elderly Posyandu activities because of the lack of family support that drove the elderly and the less explains the benefits cadres Posyandu activities so that the health condition of the elderly can not be monitored well, especially in patients with hypertension. One of the solutions in the management effort for hypertension in the elderly is the role of family support and the role of the cadre in recognizing, supervising, and taking care of the health problems in the elderly. The role of the cadre that is optimal and that is increasing the health level can control the disease in the elderly. Objective : The objective of the research was to find out the influence of the role of family support and the role of the cadre in the hypertension management effort in the Posyandu for the elderly in Puskesmas Jetis 1 Bantul. Methodology : The research was analytical survey in nature with cross sectional research design. The sample taken was 44 respondens using Total Sampling technique. The research instrument was using questionnaire and the data analysis was using Kendall Tau’s test. Result : The role of family support in the management effort for hypertension in the elderly has p value of 0,000. This showed that 0,000 < 0,05 and r count of 0,922. The role of the cadre in the management effort for hypertension in the elderly has p value of 0,000. This showed that 0,000 < 0,05 and r count of 0,734. Conclusion : There was an influence of the family support in management effort for hypertension in the elderly and it indicated the the level of the correlation was vey strong and the t count value has positif correlation direction. Meanwhile, there as also an influence of the role of the cadre in management effort for hypertension in the elderly and it indicated that the level of the correlation was strong the r count value has positive correlation direction.